ANEH TAPI NYATA: SATU GEREJA BANYAK DENOMINASI - M. Yusuf Asry (Harmoni, 2013)
In the relationship between intra and inter-faith believers there is one important problem that has to be faced, namely the establishment of houses of worship based on the joint ministerial decree signed by the Religious Affairs Ministry and the Home Affairs Ministry No. 9 and 8 2006. All religious believers have to face the same problem with different intensities. One of them is, as presented in this study, experienced by Christians with their wellknown diverse denominations. Based on theological and ritual differences, each denomination wishes to establish their own house of worship, which is now hampered by the join ministerial decree 2006. However, in some areas, the believers still uphold local wisdom which then leads to the existence of a church with different denominations. The experience of Imanuel Church Building (CGI) in Maleo Raya Bintaro Jaya, Tangerang Selatan, Banten, is interesting to note. Strange but real, one church with various denominations. How does this happen? There are no difficulties and problems in establishing the house of worship when all the requirements are fulfilled by these denominations and churches. This article provides some wise hints in handling problems of the establishment of houses of worship, a wise gesture which can be regarded as the role model in maintaining harmony.